Developing students’ academic literacy at the faculty of public administration - Evgeny V. Mironov (Высшее образование в России)
The author describes the experience accumulated by the Faculty of Public Administration of the Russian Presidential Academy of National Economy and Public Administration in creating a system of developing students’ intellectual competences and academic literacy skills. The key elements of the system are interdisciplinary courses, such as “Introduction to Critical Thinking” and “Great Books” , tutorials for students and collaboration among teachers.